Counseling addicted women : a practical guide - Cohen, Monique (Thousand Oaks, Calif. : Sage Publications, 2000)
Monique Cohen offers hands-on practical guidance to counselors, nurses, social workers, and others who help women along the journey from substance abuse to healthy and fulfilling lives. In a user-friendly format, she identifies the challenges and issues inherent in treating female substance abusers. With its exercises and activities, this volume is both a reference and a resource guide for clinicians and professionals.
Includes bibliographical references and index.
Keywords: Women -- Substance use -- Prevention; Alcoholism counseling; Drug abuse counseling